Program Skrining Kekuatan Genggaman Tangan sebagai Langkah Deteksi Dini Sarkopenia pada Dewasa - Johan Johan; Alexander HalimSantoso; Farell ChristianGunaidi; Kenzie RafifRamadhani; Disya GwynethAziel (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
Sarcopenia is a degenerative condition commonly found in the elderly, characterized by a decline in muscle mass and strength, which significantly impacts quality of life and functional ability. Muscle mass loss occurs gradually from the age of 30 and accelerates markedly after the age of 65, increasing the risk of disability, cardiovascular disease, and mortality. Early detection of sarcopenia through handgrip strength measurement is considered an effective and practical method due to its non-invasive nature and ease of application in community settings. This activity aimed to screen handgrip strength among the adult population in Cengkareng to detect potential sarcopenia and raise awareness of the importance of maintaining muscle strength. The Plan–Do–Check–Action (PDCA) approach was employed as a continuous improvement framework for the activity. The screening was conducted at Cengkareng Indah Baptist School, West Jakarta, involving 67 participants. The results showed that 25 participants (37.32%) had low handgrip strength. Handgrip strength screening is effective in identifying sarcopenia risk, enabling early interventions that can improve quality of life and prevent complications in older age.